Spectrophotometric Determination of Aluminum with Dibromo-p-sulfonic Acid Arsenazo - Zhang, Xiao-Xia; Wang, Yan-Ling; Zhao, Yan; Wang, Xiao-Ming; Zhai, Qing-Zhou (Asian Journal of Chemistry, 2011)
The colour reaction between aluminum(III) and dibromo-p-sulfonic acid arsenazo takes place to produce a purple-red complex in the buffer solution of NH4OAc-HOAc at pH 6.0. The maximum absorption wavelength of the complex is 610 nm. A good linearity is presented between absorbance and the content of Al(III) over the range of 0-1.4 μg/mL. Its linear regression equation is: A = 0.6930 C (C: μg/mL) + 0.0211, with a correlation coefficient of g = 0.9992. The detection limit of the method is 12.2 ng/mL. The present method has been successfully applied to determine aluminum in water sample, with a relative standard deviation of 2.58 % for 10 determinations. The recovery of the method was 103.1 %.